Promising development of electronic services and communication in the tax and customs sector - Hrytsyshyn, Anna; Liuba, Oksana; Liuba, Andrii (Herald of Economics, 2025)
Introduction. The intensification of reforms in the field of administrative services is accompanied by the digitalization of interaction among citizens, businesses, and fiscal institutions. The use of modern information and communication technologies forms an integrated fiscal space and creates a foundation for further improvement of tax and fee administration. Consideration of technological transformations and the interests of all participants in the tax and customs process necessitates research on promising directions for the development of electronic fiscal services.Purpose. The article aims to identify prospective directions for enhancing electronic services and communications in the tax and customs domain and to determine their impact on the administration of taxes and fees.Results. The study demonstrates the importance of further transformation of electronic services and communications in the tax and customs sphere. Three promising directions for improving electronic services in tax and fee administration are highlighted: informational integration (consolidation of diverse services on a single electronic platform, creation of an integrated informational environment, global information synchronization); technological implementation (artificial intelligence, blockchain); electronic communication (software applications for mobile platforms, chatbots, remote electronic audit). The significance of accounting information in the electronic tax and customs environment of enterprises is substantiated as a key factor for the effective functioning of all participants in the fiscal process.Prospects. The further evolution of electronic services in the tax and fiscal sphere focuses on informational integration, adoption of innovative technologies for data processing, and provision of efficient communications within the national fiscal system. However, current development trends of platforms do not resolve the problems of informational and functional interrelations between tax and customs institutions within the fiscal process, which defines the subject of future research.